Dichorisandra fadenii (Commelinaceae), a new villose species from southwestern Amazonia - Aona, Lidyanne Yuriko Saleme; Souza, Everton Hilo De; Bittrich, Volker; Amaral, Maria Do Carmo Estanislau Do (Phytotaxa, 2025)
We describe, discuss, and illustrate Dichorisandra fadenii, a new species endemic in an area of southwestern Amazonia (Brazil, Peru and Bolivia). The new species can be differentiated from its congeneric species by having villose stem and leaves, whitish flowers with six stamens, yellowish anthers, opening by 2 apical pores, and lanceoloid, acuminate fruits. Discussion of relevant characters, comparisons with similar species, description, distribution map, and illustrations are provided. The species is assessed as ‘Vulnerable’, due to its restricted and fragmented distribution and plausible threats to the habitats in Amazonian forests.